A comparison of anti-whiplash seats during low/moderate speed rear-end collisions. (2nd April 2020) - Mang, Daniel W. H.; Siegmund, Gunter P.; Blouin, Jean-Sébastien
Abstract: Objectives: The Insurance Institute for Highway Safety (IIHS) rates automotive seats as good, acceptable, marginal, and poor on their abilities to prevent whiplash injuries during rear-end collisions. The goal of this study was to compare the performance of some good- and poor-rated seats at speed changes below 16 km/h where some whiplash injuries occur. Methods: A BioRID II anthropometric test device (ATD) underwent rear-end collisions from 2 to 14 km/h while seated on one of two Volvo Whiplash Prevention seats (WHIPS), a Saab Active Head Restraint seat (SAHR), or a General Motors High Retention seat (GMHR). The WHIPS and SAHR seats were rated good whereas the GMHR seat was rated poor by the IIHS. The ATD's kinematics, kinetics and three neck injury criteria were evaluated across the range of collision severities. Results: Most of the head and torso kinematics, kinetics and injury criteria exhibited graded responses with increasing collision severities. Only head extension angle remained relatively similar across all speed changes. Differences between the good- and poor-rated seats were most apparent in the upper neck loads and moments, and head retraction for speed changes greater than 6 km/h. Conclusions: The relatively similar occupant responses across all seats could explain the marginal reductions in whiplash injury risk between good- and poor-rated seats in field studies. Further research into the design of anti-whiplash devices is required to better understand the link between occupant response and injury, and to better mitigate the risk of whiplash injuries during rear-end collisions.